Association of trough vedolizumab levels with clinical, biological and endoscopic outcomes during maintenance therapy in inflammatory bowel disease. Issue 2 (3rd July 2019) - Plevris, Nikolas; Jenkinson, Philip W; Chuah, Cher S; Lyons, Mathew; Merchant, Lynne M; Pattenden, Rebecca J; Arnott, Ian D; Jones, Gareth R; Lees, Charlie W
Abstract : Objective: To establish the relationship between trough vedolizumab levels and outcomes during maintenance therapy. Design: Cross-sectional service evaluation was performed on patients with inflammatory bowel disease (IBD) receiving maintenance vedolizumab therapy (minimum of 12 weeks following induction). Prior to infusion, data on clinical activity (Harvey-Bradshaw Index or partial Mayo score), trough C-reactive protein (CRP)/vedolizumab levels and faecal calprotectin were collected. Endoscopic data (±8 weeks from vedolizumab level testing) were obtained by review of medical records. Vedolizumab levels were processed using the Immundiagnostik monitor ELISA. Setting: The Edinburgh IBD Unit, Western General Hospital (tertiary IBD referral centre). Patients: Seventy-three patients (30 ulcerative colitis and 43 Crohn's disease) were identified who fulfilled inclusion criteria and had vedolizumab levels matched with clinical activity scores, CRP and faecal calprotectin. Of these, 40 patients also had matched endoscopic data. Main outcome measures: The association of trough vedolizumab levels with clinical remission (Harvey-Bradshaw Index <5 or partial Mayo <2), biologic remission (faecal calprotectin <250 µg/g+CRP <5 mg/L) and endoscopic remission (Mayo score 0/no inflammation and ulceration on colonoscopy). Results: The median trough vedolizumab levels were similar between patients in and not in clinical remission (10.6 vs 9.9 µg/mL, p=0.54); biologic remission (10.6 vs 9.8 µg/mL, p=0.35) and endoscopic remission (8.1 vs 10.2 µg/mL, p=0.21). Quartile analysis revealed no significant increase in the proportion of patients in clinical remission, biologic remission or endoscopic remission with increasing trough vedolizumab levels (p<0.05). Conclusions: In this cohort, trough vedolizumab levels were not associated with clinical, biological or endoscopic outcomes during maintenance therapy.